The social construction of a torture sustaining reality: A rhetorical analysis of claims-making about terrorism as a social problem in the United States post 911 - Doucette, Jason Francis (University of Ottawa (Canada), 2010)
This study examines how rhetoric was used to socially construct a torture sustaining reality in the United States after the September 11th terrorist attacks, by both print journalists and President George W. Bush's Administration. After the 9/11 attacks terrorism received wide attention from the media and public. As a result of these attacks, the United States began the ''war on terror" and invaded Afghanistan and later Iraq. During these invasions allegations of torture by the American military began to emerge. This study carries out a content analysis of claims about terrorism and responses to allegations of torture. This analysis is guided by the contextual social constructionist approach of Joel Best (1990) and Stanley Cohen's (2001) study of "denials". The contextual social constructionist approach of Best (1990) is the theoretical departure point for a sample drawn from the New York Times as well as a sample drawn from the Internet website for the Whitehouse during George W. Bush's tenure as President. A final sample drawn from the same Whitehouse website will be engaged through an amalgamation of Best's (1990) contextual social constructionist approach and Cohen's (2001) study of "denials". This study reveals that the construction of terrorism as a social problem aided the maintenance of a torture sustaining reality. This study further explains how rationalizations are used by a liberal government to maintain a torture sustaining reality through the use of rhetoric and denials. In addition, this study shows that a torture sustaining reality is supported through the mobilization of language that dehumanizes (the process of othering) those who stand in opposition to it. As well, this study demonstrates how the concepts of risk and moral panic also help to explain how this torture sustaining reality is maintained in a liberal state. Furthermore, this study also investigates the claim-making process. In pursuing these areas, the study illustrates how denials are rhetorically composed, or in other words what language is used and how it is used to form denials. More specifically, this study reveals how the rhetoric of denial is formed and shifts to support a torture sustaining reality during a claims-making episode. Secondly, claims-making about terrorism does not always follow the "typical" path of most claim-making about social problems. Claims-making about terrorism sometimes involves the "Rhetoric of Rectitude" and the "Rhetoric of Rationality", which can be intertwined to help predicate a torture sustaining reality, or may predominantly rely upon the "Rhetoric of Rectitude". Finally, this study alerts us to very paradoxical nature that freedom occupies in this world, and how easily the notion of freedom may be championed to justify atrocities.
Keywords: Political Science, General.; Sociology, Criminology and Penology.